Experimental investigation on interply friction properties of thermoset prepreg systems. (January 2019) - Pasco, Corentin; Khan, Muhammad; Gupta, Jaipal; Kendall, Kenneth
A comprehensive novel investigation into the characterisation of interply friction behaviour of thermoset prepregs for high-volume manufacturing was conducted. High interply slipping rate and normal pressure typically used for high-volume manufacturing present challenges when preforming carbon fibre reinforced plastics. The study involved multiple reinforcement architectures (woven and unidirectional with the same rapid-cure resin system) which were characterised using a bespoke interply friction test rig used to simulate processing conditions representative to press forming and double diaphragm forming. Under prescribed conditions, woven and unidirectional prepregs exhibit significantly different frictional behaviour. Results demonstrated the unidirectional material obeys a hydrodynamic lubrication mode. For the woven material, a rate-dependent friction behaviour was found at low normal pressure. At higher normal pressure however, the woven material exhibited a friction behaviour similar to that of a dry reinforcement and significant tow displacement was observed. Post-characterisation analysis of test-specimens showed significant resin migration towards the outer edges of the plies, leaving a relatively resin-starved contact interface. The findings generate new knowledge on interply friction properties of thermoset prepreg for high-volume manufacturing applications, yet reveal a lack of understanding of the influence of tow tensions as well as the pre-impregnation level for a range of processing conditions.